2018
DOI: 10.1016/j.celrep.2017.12.023
|View full text |Cite
|
Sign up to set email alerts
|

Anterior Cingulate Cortex Input to the Claustrum Is Required for Top-Down Action Control

Abstract: SUMMARY Cognitive abilities, such as volitional attention, operate under top-down, executive frontal cortical control of hierarchically lower structures. The circuit mechanisms underlying this process are unresolved. The claustrum possesses interconnectivity with many cortical areas and, thus, is hypothesized to orchestrate the cortical mantle for top-down control. Whether the claustrum receives top-down input and how this input may be processed by the claustrum have yet to be formally tested, however. We reve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

16
179
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 143 publications
(198 citation statements)
references
References 65 publications
16
179
3
Order By: Relevance
“…To directly test this, we injected equal volumes of CTB conjugated with Alexa 647, 488, or 555 into the ACA, V1, and RSP, respectively, in the same animal to retrogradely label CLA neurons that project to each of these regions (Figure a, Table ). The ACA was selected since retrograde tracer injections here have been shown to strongly label CLA neurons throughout the entire length of the structure, and the distribution of these cells has been confirmed to fall within the boundaries of the CLA as defined by dense parvalbumin (PV) immunoreactivity and Gng2 expression (Mathur et al, ; White et al, , ). Similarly, V1 was selected as it has been shown to receive CLA input, however, some reports suggest that sensory cortical regions may receive segregated inputs from discrete parts of the CLA (Kitanishi & Matsuo, ; White et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…To directly test this, we injected equal volumes of CTB conjugated with Alexa 647, 488, or 555 into the ACA, V1, and RSP, respectively, in the same animal to retrogradely label CLA neurons that project to each of these regions (Figure a, Table ). The ACA was selected since retrograde tracer injections here have been shown to strongly label CLA neurons throughout the entire length of the structure, and the distribution of these cells has been confirmed to fall within the boundaries of the CLA as defined by dense parvalbumin (PV) immunoreactivity and Gng2 expression (Mathur et al, ; White et al, , ). Similarly, V1 was selected as it has been shown to receive CLA input, however, some reports suggest that sensory cortical regions may receive segregated inputs from discrete parts of the CLA (Kitanishi & Matsuo, ; White et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…Topological distinctions can be made between prelimbic, infralimbic and anterior cingulate cortices, or even more generalised terms such as the ventromedial and dorsomedial prefrontal cortex. [211][212][213] In general, it appears that, although the mPFC exhibits a number of generalised core processes, such as having its neural ensembles exert top-down influence on lower brain regions, the part that is activated depends on the type of behaviour. 206 Previous work indicates that both the prelimbic and infralimbic cortex are important for anticipatory behaviour.…”
Section: The Medial Prefrontal Cortex (Mpfc) Is a Diverse Region Thatmentioning
confidence: 99%
“…The CLA-En boundary in primate brains is somewhat loosely defined. Using only the marmoset as an example, there are substantial regions of uncertainty which could lead to confusion and may hamper experimental progress by making it difficult to selectively target CLA versus En for injection of viral constructs, as have been employed in rodent studies (White et al, 2018). In the marmoset stereotaxic atlas of Paxinos, Charles, et al (2012a) and Paxinos, Watson, et al (2012b), the En is identified on the basis of increased cell density in the Nissl- In both New World (Reser et al, 2014(Reser et al, , 2017 and Old World monkey species (Baizer, 2014), the CLA complex is particularly well resolved by staining for myelin, which is present at much lower levels in the CLA than in the adjacent white matter tracts.…”
Section: Delineating Cla and En In Primates By Anatomical Connectivmentioning
confidence: 99%